Pengungkapan islamic social reporting yang dimoderasi komisaris independen dengan teknik moderated regression analysis - Safitri, Febrianti; Rofiuddin, Mohammad (Nur Science Institute, 2021)
The purpose of this study is to obtain empirical evidence regarding the effect of firm size, profitability, and leverage on the disclosure of Islamic social reporting (ISR) with independent commissioners as moderating variables. This study applies secondary data in the form of panel data from the annual financial statements of 11 Islamic commercial banks in 2016-2020 through the purposive sampling technique. The analytical technique used is multiple linear analysis and moderated regression analysis (MRA). The research proves that firm size and leverage variables have a positive effect on ISR; profitability harms ISR. Meanwhile, analysis through independent commissioners shows that independent commissioners are unable to moderate firm size and profitability on ISR. Meanwhile, independent commissioners can moderate leverage on ISR.